The Concept The Concept of Islamic Religious Education in Ki Hajar Dewantara’s Thought and Its Relevance in the Digital Era - Mahariani; La Karim; Amirul Salam; Rasidah (Jurnal Pendidikan Edutama, 2025)
This article examines the concept of Islamic religious education from the perspective of Ki Hajar Dewantara's thought and explores its relevance in the current digital era. Ki Hajar Dewantara, as a pioneer of Indonesian national education, is known for his educational philosophy that emphasizes character formation, freedom of thought, and commitment to humanistic and cultural values. Although he did not explicitly formulate a model of Islamic religious education, his ideas are rich in religious values and spirituality aligned with Islamic principles, such as freedom in learning (the among system), teacher as role model, and the balance between intellectual, emotional, and volitional development. These are encapsulated in three core values: ing ngarsa sung tuladha (in front, setting an example), ing madya mangun karsa (in the middle, inspiring initiative), and tut wuri handayani (at the back, providing support). In the digital era, marked by information disruption, changes in social interaction patterns, and the rise of online learning platforms, Ki Hajar Dewantara's educational values have become increasingly relevant. This article highlights how his educational principles can be integrated into digital Islamic religious education through a holistic, humanistic, and contextual approach. The study uses a literature review method with qualitative analysis of Ki Hajar Dewantara’s works and contemporary literature on religious education and digital technology. The analysis shows that his ideas can serve as a strong philosophical foundation for developing a model of Islamic religious education that is technologically adaptive yet firmly rooted in noble values. Therefore, his ideas are not only historically relevant but also strategically significant for addressing the challenges of Islamic education in the digital age.